STRATEGIC GUIDELINES FOR THE DEVELOPMENT OF THE FOREIGN ECONOMIC ACTIVITY OF ENTERPRISES IN THE BANI ENVIRONMENT - MOTUZKA, Olena; HRYNCHAK, Nataliia (Herald of Khmelnytskyi National University. Economic sciences, 2023)
Recently, the foreign economic activity of enterprises has been characterized by a decrease in the volume of world trade, the introduction of trade restrictions and a change in the trade policy of countries. In an environment where retail businesses are forced to cease operations or close, especially after the onset of the COVID-19 pandemic, trading in the BANI environment provides an opportunity to increase revenue, attract new customers and stimulate a change in distribution channels. This determines the relevance of the analysis of the impact of the BANI era on world trade, and therefore on foreign economic activity.The article presents the results of the study of the foreign economic activity of enterprises in the BANI environment. The meaning of the acronym BANI is revealed, it is emphasized that one of the main factors in the emergence of the BANI era was the COVID-19 pandemic. It is emphasized that it is small enterprises, in particular in the field of foreign economic activity, that face the biggest problems in the current changing environment: they are more sensitive to changes and worse adapt to them, having fewer resources in their arsenal, and free capital that can be used for amelioration of the negative consequences of the BANI era, they are practically absent. The risks of foreign economic activity of small business entities in the BANI environment have been determined. A list of anti-crisis measures to overcome the negative impact of the BANI era on foreign economic activity is provided. The importance of innovative activity at small enterprises in the field of foreign economic activity for their adaptation in the BANI environment is emphasized. It is shown that one of the effective innovative approaches for enterprises of foreign economic activity in the BANI environment is the introduction of virtual entrepreneurship, since it is this, especially at the international level, that contributes to:1) integration of the efforts of partner enterprises around a specific project, which is not able to be implemented by each individual enterprise;2) expands the boundaries of a traditional enterprise and completely eliminates spatial barriers.It was emphasized that one of the priority tasks in the era of BANI is the development of an effective legal mechanism for ensuring the information security of subjects of foreign economic activity. The role of WTO agreements in ensuring the transparency of international trade relations in the BANI environment is outlined.
Keywords: virtual entrepreneurship; foreign economic activities; small enterprises; BANI environment